T cell‐inflamed gene expression profile is associated with favorable disease‐specific survival in non‐hypermutated microsatellite‐stable colorectal cancer patients. (7th November 2022) - Yin, Hang; Harrison, Tabitha A.; Thomas, Sushma S.; Sather, Cassie L.; Koehne, Amanda L.; Malen, Rachel C.; Reedy, Adriana M.; Wurscher, Michelle A.; Hsu, Li; Phipps, Amanda I.; Zaidi, Syed H. E.; Newcomb, Polly A.; et al.
Abstract: Background: The anti‐tumor immune response plays a key role in colorectal cancer (CRC) progression and survival. The T cell‐inflamed gene expression profile (GEP) is a biomarker predicting response to checkpoint inhibitor immunotherapy across immunogenic cancer types, but the prognostic value in CRC is unknown. We evaluated associations with disease‐specific survival, somatic mutations, and examined its differentially expressed genes and pathways among 84 sporadic CRC patients from the Seattle Colon Cancer Family Registry. Methods: Gene expression profiling was performed using Nanostring's nCounter PanCancer IO 360 panel. Somatic mutations were identified by a targeted DNA sequencing panel. Results: The T cell‐inflamed GEP was positively associated with tumor mutation burden and microsatellite instability high (MSI‐H). Higher T cell‐inflamed GEP had favorable CRC‐specific survival (hazard ratio [HR] per standard deviation unit = 0.50, p  = 0.004) regardless of hypermutation or MSI status. Analysis of recurrently mutated genes having at least 10 mutation carriers, suggested that the T cell‐inflamed GEP is positively associated with RYR1, and negatively associated with APC . However, these associations were attenuated after adjusting for hypermutation or MSI status. We also found that expression of genes RPL23, EPCAM, AREG and ITGA6, and the Wnt signaling pathway was negatively associated with the T cell‐inflamed GEP, which might indicate immune‐inhibitory mechanisms. Conclusions: Our results show that the T cell‐inflamed GEP is a prognostic biomarker in non‐hypermutated microsatellite‐stable CRC. This also suggests that patient stratification for immunotherapy within this CRC subgroup should be explored further. Moreover, reported immune‐inhibitory gene expression signals may suggest targets for therapeutic combination with immunotherapy. Abstract : T cell‐inflamed gene expression profile score, a biomarker predicting immune checkpoint inhibitor responses, is related to colorectal cancer (CRC)‐specific survival among non‐hypermutated and microsatellite stable patients, a group refractory to immunotherapy. Our finding suggests that patient stratification for immunotherapy within this CRC subgroup should be explored further.